Management of dystocia due to an ischiopagus monster in crossbred cow and its correction with subcutaneous fetotomy - A case report - Kumar, Pramod; Dholpuria, Sandeep; Satish; Kumar, Tapendra; Pooja; Kumawat, Babulal (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A crossbred cow in her third parity was presented in the clinics with history of complete gestation period and dystocia. The three limbs were protruding through the vulva without further progress in delivery in spite of traction applied by local area veterinarian. Per vaginum examination revealed fetal monstrosity and a decision to perform subcutaneous fetotomy was taken which resulted in delivery of an ischiopagus monster.